Age Differences in Processes Underlying Hindsight Bias: A Life-Span Study. Issue 3 (27th May 2018) - Pohl, Rüdiger F.; Bayen, Ute J.; Arnold, Nina; Auer, Tina-Sarah; Martin, Claudia
ABSTRACT: Hindsight bias is the tendency to overestimate one's prior knowledge of a fact or event after learning the actual fact. Recent research has suggested that age-related differences in hindsight bias may be based on age-related differences in inhibitory control. We tested whether this explanation held for 3 cognitive processes assumed to underlie hindsight bias: recollection bias, reconstruction bias, and the tendency to adopt newly acquired knowledge as old. We performed a typical hindsight-bias study with 9-year-olds, 12-year-olds, young adults, and older adults. Participants first gave numerical judgments to difficult almanac questions. They later received the correct judgments for some of the questions while trying to recall their own earlier judgments. To experimentally test the impact of inhibitory control, the correct judgment was presented either in a weak or in a strong manner that was difficult to ignore. Hindsight bias was larger in the strong condition than in the weak condition and followed a U-shaped life-span pattern with young adults showing the least hindsight bias in line with an inhibitory-control explanation. Yet, the mixture of underlying processes differed considerably between age groups, so inhibitory control did not suffice as a sole explanation of age differences.